Association between functional SIRT1 polymorphisms and the clinical characteristics of patients with autoimmune thyroid disease. (3rd July 2016) - Sarumaru, Mika; Watanabe, Mikio; Inoue, Naoya; Hisamoto, Yuko; Morita, Emi; Arakawa, Yuya; Hidaka, Yoh; Iwatani, Yoshinori
Abstract: Sirtuin1 (SIRT1) is a Class 3 nicotinamide adenine dinucleotide-dependent histone deacetylase (HDAC) that is thought to be implicated in the protection against autoimmune diseases. However, an association between SIRT1 and autoimmune thyroid disease (AITD) has not been reported. In this study, we selected four single nucleotide polymorphisms (SNPs) in the SIRT1 gene, rs12049646 T/C (termed SNP1), rs12778366 T/C (termed SNP2), rs3758391 T/C (termed SNP3), and rs4746720 T/C (termed SNP4). We genotyped each of these polymorphic sites in 185 patients with Graves' disease (GD), including 76 patients with intractable GD and 57 patients with GD in remission; 151 patients with Hashimoto's disease (HD), including 68 patients with severe HD and 54 patients with mild HD; and 96 healthy volunteers. SNP1 and SNP3 were genotyped by the PCR-RFLP method; SNP2 and SNP4 were genotyped using TaqMan® SNP genotyping assays. We also measured the levels of SIRT1 mRNA in CD4 + T cells from 18 control subjects, 16 patients with GD in remission and 14 patients with mild HD using a real-time PCR method. In patients with GD and HD, the C carriers (TC + CC genotypes) of SNP3 showed significantly higher titers of McAb than the TT genotype ( p  = 0.0261 and p  = 0.0309, respectively). Additionally, the T carriers (TT + TC genotypes) of SNP4 showed significantly higher titers of McAb than the CC genotype in patients with GD ( p  = 0.0079). In conclusion, the polymorphisms in the SIRT1 gene were associated with a greater production of thyroid autoantibodies.